Music Therapy in the Psychosocial Treatment of Adult Cancer Patients: A Systematic Review and Meta-Analysis - Köhler, Friederike; Martin, Zoe-Sofia; Hertrampf, Ruth-Susanne; Gäbel, Christine; Kessler, Jens; Ditzen, Beate; Warth, Marco (Frontiers in Psychology, 2020)
Introduction Music therapy is used as an adjunct oncological treatment aiming at the improvement of psychological and physical well-being through music. A growing body of randomized and non-randomized controlled trials has been published and reviewed recently. However, a global, quantitative assessment of the effectiveness of music therapy in adult cancer care is missing. The present study thus aims to synthesize the evidence of music therapy in different oncological treatment phases. Methods We conducted a pre-registered systematic review and meta-analysis (PROSPERO-ID: CRD42019133084) following standard guidelines. We searched electronic databases for studies on music therapy performed by a therapist with adult cancer patients. Results The narrative synthesis included thirty studies showing that music therapy overall had positive effects on a broad range of outcomes, with techniques and effects varying in different phases. During curative treatment, results were most promising with regard to anxiety, depression, and pain medication intake, while in palliative settings, improvements with regard to quality of life, spiritual well-being, pain, and stress were reported. Twenty-one studies were included in the meta-analysis which showed small but significant effects of music therapy on psychological well-being (d = 0.35, p < .001), physical symptom distress (d = -0.26, p = .017), and quality of life (d = 0.36, p = .023). Heterogeneity between effect sizes was small to medium. Moderator analyses identified studies with a single session of music therapy and the use of receptive techniques to produce larger effects regarding psychological well-being. Conclusion Music therapy can improve relevant health-outcomes in cancer patients and should therefore be offered in various treatment phases. Future research should include potential moderators such as individual information about patients to find out who benefits most from different kinds of music therapy.